2017
DOI: 10.1016/j.smim.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Natural Killer cell immunotherapy to the tumour microenvironment

Abstract: Natural killer (NK) cells are cytotoxic and cytokine-secreting cells that can mediate potent anti-tumour activity. Accumulating evidence indicates that NK cell functions are severely compromised within the confines of the tumour microenvironment thus impairing the efficacy and development of NK cell-based therapies. Here we review the various cellular and molecular pathways that tumours have supplanted to evade NK cell surveillance. We highlight novel strategies designed to alleviate or circumvent the immunosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 107 publications
(109 reference statements)
0
25
0
Order By: Relevance
“…Histological analysis of tumor-infiltrating lymphoid cells has been proven to be a reliable and prognostically relevant marker ( Galon et al, 2014 ; Denkert et al, 2016 ; International TILs Working Group 2014 et al, 2015 ). Antitumor immunity arises in a complex ecosystem of various cell types that closely interact with one another, such as effector lymphocytes ( Li et al, 2016 ), macrophages ( Halama et al, 2016 ; Biswas and Mantovani, 2010 ), dendritic cells ( Gardner and Ruffell, 2016 ), granulocytes ( Coffelt et al, 2016 ), innate lymphoid cells ( Crome et al, 2017 ), regulatory T cells ( Nishikawa and Sakaguchi, 2010 ), natural killer cells ( Crome et al, 2013 ; Barrow and Colonna, 2017 ), myeloid-derived suppressor cells ( Talmadge and Gabrilovich, 2013 ) and other cell types ( Kather et al, 2017 ). In tumor tissue, T lymphocytes (T cells) and macrophages are among the most abundant immune cells and are closely related to clinical outcome ( Fridman et al, 2017 ; Kather et al, 2017 ; Fridman et al, 2012 ; Kather et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…Histological analysis of tumor-infiltrating lymphoid cells has been proven to be a reliable and prognostically relevant marker ( Galon et al, 2014 ; Denkert et al, 2016 ; International TILs Working Group 2014 et al, 2015 ). Antitumor immunity arises in a complex ecosystem of various cell types that closely interact with one another, such as effector lymphocytes ( Li et al, 2016 ), macrophages ( Halama et al, 2016 ; Biswas and Mantovani, 2010 ), dendritic cells ( Gardner and Ruffell, 2016 ), granulocytes ( Coffelt et al, 2016 ), innate lymphoid cells ( Crome et al, 2017 ), regulatory T cells ( Nishikawa and Sakaguchi, 2010 ), natural killer cells ( Crome et al, 2013 ; Barrow and Colonna, 2017 ), myeloid-derived suppressor cells ( Talmadge and Gabrilovich, 2013 ) and other cell types ( Kather et al, 2017 ). In tumor tissue, T lymphocytes (T cells) and macrophages are among the most abundant immune cells and are closely related to clinical outcome ( Fridman et al, 2017 ; Kather et al, 2017 ; Fridman et al, 2012 ; Kather et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these mechanisms are represented by the inhibition of tumor antigen presentation, expression of immune checkpoint ligands as programmed death ligand-1 (PD-L1), secretion of suppressive factors like interleukin (IL)-10, soluble human leukocyte antigen (HLA)-G, transforming growth factor (TGF)-β, indoleamine 2,3-dioxygenase (IDO), recruitment and polarization of immunosuppressive cells as macrophages, regulatory T cells (Tregs), myeloid derived suppressor cells (MDSC), and mesenchymal stromal cells (MSC). Altogether these cells, with the tumor cells themselves, are present inthe tumor microenvironment (TME) [ 7 , 8 , 9 , 10 , 11 ] ( Figure 1 ). Another major molecular mechanism used by tumor cells to impair NK cell recognition and activation is based on the expression of inhibitory (as major histocompatibility complex (MHC) class I molecules) and the release in a soluble form of ligands (such as MHC class I polypeptide–related sequence (MIC) A/B and UL16 binding protein (ULBP1-6) for NK cell-activating receptors [ 12 , 13 ].…”
Section: Tumor-mediated Nk Cell Exhaustion In Hematological Malignmentioning
confidence: 99%
“…ILT-2/HLA-G interaction impairs several functions on NK cells, such as cytokine secretion, chemotaxis, and the immunological synapse formation between NK cells and their target [ 115 ]. Of note, HLA-G belongs to the immunosuppressive factors secreted by the TME components in hematological malignancies, which contributes to the immune evasion of tumor cells [ 7 , 8 , 9 , 10 , 11 , 115 , 116 ]. Although it has been reported that Lenalidomide decreases the expression of ILT-2 on CLL cells, thus promoting NK cell proliferation and activation [ 117 ], today, there are no clinical studies evaluating the possible inhibition of HLA-G (or its receptors) in NK cell-based immunotherapy in hematological malignancies.…”
Section: Current Advanced Therapy In Hematological Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…atural killer cells are innate lymphocytes with cytotoxic capacity toward virus-infected, transformed, or stressed cells (1,2). Hence, there is continued interest to harness NK cells for cancer immunotherapy (3)(4)(5). Furthermore, NK cells are important producers of cytokines, such as IFN-g and TNF, thereby modulating immune responses and contributing to tissue homeostasis (6)(7)(8).…”
mentioning
confidence: 99%